Prompt enhancement of the Earth's outer radiation belt due to substorm electron injections. Issue 12 (17th December 2016) - Tang, C. L.; Zhang, J.‐C.; Reeves, G. D.; Su, Z. P.; Baker, D. N.; Spence, H. E.; Funsten, H. O.; Blake, J. B.; Wygant, J. R.
Abstract: We present multipoint simultaneous observations of the near‐Earth magnetotail and outer radiation belt during the substorm electron injection event on 16 August 2013. Time History of Events and Macroscale Interactions during Substorms A in the near‐Earth magnetotail observed flux‐enhanced electrons of 300 keV during the magnetic field dipolarization. Geosynchronous orbit satellites also observed the intensive electron injections. Located in the outer radiation belt, RBSP‐A observed enhancements of MeV electrons accompanied by substorm dipolarization. The phase space density (PSD) of MeV electrons at L * 5.4 increased by 1 order of magnitude in 1 h, resulting in a local PSD peak of MeV electrons, which was caused by the direct effect of substorm injections. Enhanced MeV electrons in the heart of the outer radiation belt were also detected within 2 h, which may be associated with intensive substorm electron injections and subsequent local acceleration by chorus waves. Multipoint observations have shown that substorm electron injections not only can be the external source of MeV electrons at the outer edge of the outer radiation belt ( L * 5.4) but also can provide the intensive seed populations in the outer radiation belt. These initial higher‐energy electrons from injection can reach relativistic energy much faster. The observations also provide evidence that enhanced substorm electron injections can explain rapid enhancements of MeV electrons in the outer radiation belt. Key Points: Simultaneous observations of the outer radiation belt and the near‐Earth tail during a substorm electron injection event The higher‐energy electrons from injection can reach relativistic energy within an hour or two Enhanced substorm electron injections can explain rapid enhancement of the outer radiation belt